The Concept of Managing the Agro-Industrial Cluster Development - ZAVYALOV, Dmitriy Vadimovich; SAGINOVA, Olga Vitalevna; ZAVYALOVA, Nadezhda Borisovna (Journal of Environmental Management and Tourism; Vol 8 No 7 (2017): JEMT Volume VIII Issue 7(23) Winter 2017, 2017)
In recent years the concept of ‘digital economy’ is present in the economy and practical activities of many countries. Modern information technologies were able not only to transform methods of data collection, transformation, storage and processing to obtain new knowledge, but also to influence economic processes, including the principles of interaction of economic agents. Producers and the end users, state structures and business entities can contact, bypassing long chains of intermediaries. The penetration of digital technologies into life is one of the characteristic features of the future world. Agro-industrial business, which is a strategic segment of the Russian economy and has a significant export potential, cannot stay away from world trends. The article presents the concept of managing the development of agro-industrial clusters as self-organizing structures of agro-industrial business that are able to integrate the activities of small and medium-sized businesses into the value-added chain using modern information technologies. The paper discloses the mandatory and supporting tools and mechanisms for implementing the concept aimed at eliminating the problems existing in the way of agro-industrial cluster formation. The definition of the term ‘agro-industrial cluster’ has been clarified; the notion of ‘digital agribusiness cluster’ has been introduced into circulation. The conceptual model of a digital cluster as the main tool for cluster members’ collaboration is presented.